HUBUNGAN TINGKAT PENDIDIKAN IBU PREMENOPAUSE DENGAN TINGKAT KECEMASAN MENGHADAPI MENOPAUSE DI DESA PELUMUTAN KABUPATEN PURBALINGGA - Fauziah Hanum Nur Adriyani (Viva Medika, 2009)
Someone who is anxious in undergoing menopause, in general do not get theright information about menopause so that dibayangkannya is the negative effects thatwill affect them after the menopausal changes depends very much on the views of eachof the women against menopouse, including knowledge about menopouse. A goodknowledge about menopause will help women understand and prepare to undergomenopause. This research aims to know the relationship between the level of educationof the mother pramenopause with menopause face a level of anxiety in Pelumutanvillage of Purbalingga in 2011. Type of this research is a Survey of analytical approachto the study of cross sectional. The sampling technique with Random Sampling, largesamples in this research was 74 people. Types of primary data obtained from thequestionnaire results. Kendal tau test based on the obtained results z z > count table (8.399 > – 1.64,p value 0.000, τ = 0.05 <-0,677), so that there is a significant relationship between theeducational level of the mother's anxiety level with premenopausal in dealing withmenopause. From this research it can be concluded that, the higher the mother's level ofeducation is low then the premenopausal levels of anxiety in the face of menopause. Key words: Relationship, pramenopause, Mother's education level of anxiety.